ChemInform Abstract: Benzothiadiazole‐Based Dyes that Emit Red Light in Solution, Solid and Liquid State. Issue 14 (8th April 2014) - Ishi‐i, Tsutomu; Sakai, Miki; Shinoda, Chihiro
Abstract The preparation and red‐light‐emitting behavior of benzothiadiazole‐tris(alkyloxy)phenylene dyes (I) are reported.